Mask Up: Exploring Cross-Cultural Influences on Mask-Making Behavior During the COVID-19 Pandemic. (October 2021) - Hahn, Kim H. Y.; Bhaduri, Gargi
At the beginning of the COVID-19 pandemic, people from around the world made numerous homemade masks for themselves and their community due to shortage of medical masks as well as to stop the spread of COVID-19. The purpose of the current study was to conduct cross cultural exploration of the reasons for making masks, self-construal and wellbeing associated with masks making by collecting data from residents across US, India, and China. The finding of this study presented different reasons for making masks as well as self-construal, and wellbeing in people who made masks versus those who did not. Differences were also observed among three different cultural groups. This study offers a unique contribution to the public health research engaging in craft making related activities to gain a better perspective of the state of health of a population and the understanding of cross-cultural study of craft making behavior during the pandemic.